Psychological well-being as correlates to organizational commitment basis for enriched wellness program - Lagan, Mary Kathleen V. (Enderun Colleges Scholarly Review, 2019)
The study was conducted to examine the correlation of psychological well-being and organizational commitment as the basis for enriched wellness programs among 100 Social Health Workers and Family Welfare Assistants in the Department of Social Welfare and Development in National Capital Region. It is based on the notion that the success of an organization comes with the contributed effort of every employees that have given their best to work hard, committed in their jobs, have a clear vision of their mandates, and functioning well in their working environment. To sustain this kind of employees there is a need to have an established and reliable Human Resources (HR) Management that will ensure to address properly the work-related concerns of employees and implement a relevant wellness program to enhance their psychological well-being that will lead to quality work output and excellent services. Based on the mean scores of the components of psychological well-being, the positive relations with others got the highest mean score followed by personal growth and self-acceptance. However, the three components which are in bottom ranked are the purpose in life, autonomy, and environmental mastery. The results of the mean scores of organizational commitments to its components that got the highest mean score were the normative commitment while the continuance commitment got the lowest mean score.